THE HEAD OF RAUDHATUL ATHFAL'S SUPPORTIVE BEHAVIOR PRACTICES IN THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM - Wiyani, Novan Ardy; Mulyani, Novi (THUFULA, 2023)
This study aims to describe and analyze the practice of supportive behavior by the head of RA Nurul Dzikri in the implementation of the independent curriculum. This study uses a qualitative research approach and a type of phenomenological research. Informants in this research included the headmaster and teachers at RA Nurul Dzikri. Data was collected by interview, observation, and documentation techniques and then analyzed using the data analysis technique of Miles and Huberman's model consisting of data reduction, data display, and verification stages. Based on the research results, it can be seen that the practice of supportive behavior towards teachers in the implementation of the independent curriculum at RA Nurul Dzikri is carried out through efforts, namely: (1) Establishing a working relationship with teachers in implementing the independent curriculum; (2) Assisting teachers in implementing the independent curriculum; (3) Listening to the teacher's ideas in implementing the independent curriculum; (4) Motivating, encouraging and praising teachers in implementing the independent curriculum; and (5) Encouraging teachers to try using new methods or strategies in implementing the independent curriculum. These five efforts have made teachers feel that their ideas and creativity are valued by their leaders, have helped teachers in their work, and have created harmonious relationships so that teachers can work on implementing an independent curriculum with high work motivation.